2022
DOI: 10.1002/cnma.202100527
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Lithium‐Ion Batteries with Long‐Term Cycling Performance Based on Titanium Carbide/3D Interconnected Porous Carbon

Abstract: Carbon-based materials are a new class of highly conductive materials that have shown cutting-edge performance in energy storage. However, the lack of a rational design for three-dimensional (3D) structures continues to limit its performance in lithium-ion batteries (LIBs). Herein, we report a 3D layered titanium carbide (TiC) prepared by a facile onepot carbonization treatment. This as-prepared TiC anode has unique continuous 3D architecture, embedded with nanodots and surface oxygenated defects that can prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Also, there is a significant difference between the first and subsequent cycles. It is noted that a well-defined reduction peak is located at ∼0.67 V in the first cycle and disappears in the subsequent cycles for the cathodic curves of all the electrodes, which can be attributed to solid electrolyte interface (SEI) layer formed on the surface of active particles due to the decomposition of the electrolyte . Meanwhile, the cathodic peaks at ∼1.45 ∼1.15, and ∼1.7 V for three electrodes in the first cycle may be assigned to the side reactions between Li + with TiC or some residual titanium-based oxides .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, there is a significant difference between the first and subsequent cycles. It is noted that a well-defined reduction peak is located at ∼0.67 V in the first cycle and disappears in the subsequent cycles for the cathodic curves of all the electrodes, which can be attributed to solid electrolyte interface (SEI) layer formed on the surface of active particles due to the decomposition of the electrolyte . Meanwhile, the cathodic peaks at ∼1.45 ∼1.15, and ∼1.7 V for three electrodes in the first cycle may be assigned to the side reactions between Li + with TiC or some residual titanium-based oxides .…”
Section: Resultsmentioning
confidence: 91%
“…It is noted that a well-defined reduction peak is located at ∼0.67 V in the first cycle and disappears in the subsequent cycles for the cathodic curves of all the electrodes, which can be attributed to solid electrolyte interface (SEI) layer formed on the surface of active particles due to the decomposition of the electrolyte. 31 Meanwhile, the cathodic peaks at ∼1.45 ∼1.15, and ∼1.7 V for three electrodes in the first cycle may be assigned to the side reactions between Li + with TiC or some residual titaniumbased oxides. 16 In the following cycles, the broad redox peaks at ∼0.77/1.0 V for TiC nanomaterials from all the CV curves may be associated with the insertion and desertion of Li ions into TiC interlayers without phase transition (eq 4).…”
Section: Electrochemical Measurementsmentioning
confidence: 95%
“…This variation can be attributed to the different production modes. 31 Figures S3b and S4 display the 1 H NMR and 13 C NMR spectra and thermogravimetric analysis results of the BDC prepared through PET chemical degradation. The results showed that the prepared BDC was relatively pure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The liquid products of PET degradation were qualitatively analyzed using gas chromatography−mass spectrometry (GC-MS) using a TR-5 capillary column with dimensions of 30 m × 0.25 mm × 0.25 μm. 1 H NMR and 13 C NMR spectra were provided via a Bruker spectrometer (MSL 400). Electrochemical Measurements.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation